Averting neonatal abstinence syndrome and treating addiction among rural, opioid‐using young women. Issue 5 (9th May 2022) - Cooper, Robert L.; Crosby, Richard A.; Martin, Peter R.; Edgerton, Ryan
Abstract: Background and Objectives: America's opioid epidemic has spawned an epidemic of neonatal abstinence syndrome (NAS). Studies have not tested approaches to promoting contraceptive services for women with opioid use disorder (OUD) along with treatment for this disorder. This pilot study examined the promotion of medication for OUD (MOUD) treatment and contraception use, primarily long‐acting reversible contraception (LARC), for women with OUD. Methods: In Appalachia, a peer‐delivered contraception and MOUD promotion intervention was delivered to a sample of 30 women with OUD. Primary outcomes were attendance of initial appointments to receive MOUD and counseling about contraceptive options. Peer recovery coaches also offered to help the women schedule appointments and attend the appointment with them or give them a ride if necessary and requested by the patients. Results: Two‐thirds experienced all seven symptoms of opioid dependence. Within 30 days of a brief counseling session, over one‐half of the women (56.7%) were referred to MOUD, with all of them initiating treatment within 30 days. Just under one‐half of the women (46.7%) were referred to a contraception consultation, with 85.7% of those receiving a LARC implant. Discussions and Conclusions: Study findings indicate the potential efficacy of a single‐session, peer‐delivered counseling intervention for linking women with OUD and at high risk of unintended pregnancy to MOUD and to services that provide women with highly reliable contraceptives. Scientific Significance: This study is unique in exploring the efficacy of linking high‐risk opioid‐using women to contraceptive options and treatment for MOUD to prevent NAS.